Filsafat Spiritualisme Kuno & Filsafat Pendidikan dalam Pandangan Socrates, Plato dan Aristoteles - Rahmat; Mustham, Zulkifli; La Hadisi (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Ancient spiritualism philosophy and the ideas of classical Greek philosophers such as Socrates, Plato, and Aristotle constitute an important foundation in the development of educational philosophy. Ancient spiritualism positions the soul as the deepest essence of human existence and the primary source of truth and moral values, while Greek philosophers developed educational concepts oriented toward the formation of reason, morality, and character. This study aims to describe the concept of ancient spiritualism philosophy and to analyze the educational perspectives of Socrates, Plato, and Aristotle within a philosophical framework of education. This research employs a qualitative descriptive library research method by examining classical philosophical sources and educational literature. The findings reveal that ancient spiritualism regards the soul as the highest human essence; Socrates emphasizes moral education through reflective dialogue; Plato views education as the ascent of the soul toward the world of ideas and the highest good; and Aristotle affirms education as a rational and moral process shaped through habituation and experience. These perspectives collectively form the conceptual basis of modern humanistic education, which emphasizes the balance between intellectual development, moral formation, and character building.